Independent assessment of a point of care HCV RNA test by laboratory analytical testing and a prospective field study in the U.S. - Lesley S Miller; Anuradha Rao; Karlyn Tunnell; Yun F Wang; Richard Parsons; Kaleb McLendon; Leda Bassit; Mahi Patel; Heather B Bowers; Courtney Sabino; Thanuja Ramachandra; Farzan Saeed; et al. (PLoS ONE)
Improvements in HCV testing, including Point of Care (POC) HCV RNA tests, are necessary to eliminate HCV. With this goal in mind, we established methods to collect capillary whole blood (CWB) via fingerstick, ensured its stability in a microtainer, and determined limit of detection (LoD) for various HCV genotypes. Next, we conducted a prospective study where CWB samples were collected from a cohort of 109 adult subjects at a safety-net hospital and tested for HCV RNA using the Xpert® HCV test on the GeneXpert® Xpress system and the cobas® HCV platform. We consistently obtained 250 μl CWB which was stable for up to 5 hours in the microtainer. Laboratory LoD studies demonstrated that the Xpert® HCV test could detect most HCV genotypes to <100 IU/ml in CWB. In the prospective clinical study, 89 subjects (82%) with valid Xpert® and cobas® HCV comparator results were analyzed. Using Xpert®, 16 out of 89 (18%) subjects had detectable HCV RNA and 73 (82%) had undetectable HCV RNA. Using cobas, 17 out of 89 (19%) participants had detectable HCV RNA, and 72 (81%) were undetectable. One sample was detectable on cobas but not Xpert®, yielding a sensitivity of 94% and specificity of 100%. This study demonstrates the feasibility of HCV RNA testing at POC using CWB obtained by fingerstick and provides preliminary data on the accuracy of the Xpert® HCV test performed by untrained operators in a CLIA-waived setting.